Mode of insertion of lipopolysaccharide into the outer membrane of escherichia coli. - Kulpa, C F (1976)
A mutant of Escherichia coli that lacks uridine 5'-diphosphate galactose-4-epimerase makes lipopolysaccharide with less carbohydrate than the parent, unless galactose is present during growth. Carbohydrate is dense, and the outer membrane, which contains lipopolysaccharide, was found to be denser when isolated from cells grown with galactose then when galactose was omitted. Cells given galactose after growth in its absence rapidly formed dense regions within the outer membrane that disappeared when galactose was removed. These results indicate that lipopolysaccharide enters the outer membrane nonrandomly at a minimum of 10 to 22 discrete "insertion points." Isopycnic centrifugation provides a method for isolating these regions.